2010
DOI: 10.1037/a0019858
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of partner violence perpetrators among male and female psychiatric patients.

Abstract: The goal of this naturalistic study was to examine heterogeneity among female and male civil psychiatric patients with a history of intimate partner violence (IPV) perpetration. Participants were 567 patients drawn from the MacArthur Violence Risk Assessment Study (J. Monahan et al., 2001). The authors examined subtype composition among 138 women and 93 men with positive histories of IPV and compared these groups with 111 women and 225 men with no histories of IPV. Findings for men and women were consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 95 publications
(125 reference statements)
7
91
1
6
Order By: Relevance
“…More recently, however, a study of 567 male and female psychiatric patients (231 with a history of IPV perpetration and 336 without such history) found evidence for all three HoltzworthMunroe and Stuart's (2014) subtypes among the women as well as the men. Although rates of IPV recidivism were about the same across subtypes for the male sample, the rates for generally violent women were twice those for the family-only type (Walsh et al, 2010).…”
Section: Differential Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…More recently, however, a study of 567 male and female psychiatric patients (231 with a history of IPV perpetration and 336 without such history) found evidence for all three HoltzworthMunroe and Stuart's (2014) subtypes among the women as well as the men. Although rates of IPV recidivism were about the same across subtypes for the male sample, the rates for generally violent women were twice those for the family-only type (Walsh et al, 2010).…”
Section: Differential Treatmentmentioning
confidence: 97%
“…A limitation of these typologies is that they focus on only one part of the relationship dyad, although Walsh et al (2010) did note that many of the borderline female perpetrators in their sample were also IPV victims, as were many of the generally violent men. The now well-known typology first proposed by Michael Johnson was derived from criminal as well as community samples and posits four separate categories based on physical violence, emotional abuse and controlling behaviors, and the extent to which the violence is unilateral or bidirectional (Johnson & Leone, 2005;Kelly & Johnson, 2008).…”
Section: Differential Treatmentmentioning
confidence: 99%
“…Interestingly, in a study with a sample of men in treatment for intimate partner violence it was reported that 40% had partners who initiated the violence (Gondolf, 1996). In humans, perpetration of intimate partner violence has been related to personality disorders in men (Edwards et al, 2003), and more recently in women (Walsh et al, 2010). Furthermore, exposure to childhood trauma increases the risk to develop both, personality disorders and intimate partner violence (Beauchaine et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in studies with batterers conducted in prison, where reports of more severe violence are expected. For instance, using the typology of Holtzworth-Munroe and Stuart, Walsh et al (2010) found the same levels of physical violence for the generally violent/antisocial group (with longer criminal history) and the family-only violent group in a sample of civil-psychiatric patients. As it is discussed below, criminology literature on crime specialization provides theoretical arguments to anticipate that family-only batterers could be also involved in moderate to severe violence toward their partners.…”
Section: Severity Of Violence and Criminal Historymentioning
confidence: 99%
“…The Holtzworth-Munroe and Stuart's batterer typology, as well as others, emphasizes the role of psychopathology to differentiate between groups of batterers. In their follow up of batterers, however, Holtzworth-Munroe et al (2003) found that the generally violent and dysphoric/borderline groups were almost indistinguishable (see also Delsol, Margolin, & John, 2003;Holtzworth-Munroe & Meehan, 2004) and that level of psychopathy in these groups were similar (Holtzworth-Munroe, Meehan, Herron, Rehman, & Stuart, 2000;Huss, Covell, & LanghinrichsenRohling, 2006;Walsh et al, 2010). While the empirical evidence suggests that psychopathology could be on the onset of partner violence for some individuals, it might not allow to clearly distinguish between subgroups of batterers (dysphoric/borderline and generally violent/antisocial in Holtzworth-Munroe and Stuart's typology; moderate and high-risk batterer in Cavanaugh and Gelles' typology).…”
Section: Severity Of Violence and Psychopathologymentioning
confidence: 99%